What's Psychology Worth? A Field Experiment in the Consumer Credit Market - Marianne Bertrand; Dean S. Karlan; Sendhil Mullainathan; Eldar Shafir; Jonathan Zinman (Yale University, Economic Growth Center, 2005)
Numerous laboratory studies report on behaviors inconsistent with rational economic models. How much do these inconsistencies matter in natural settings, when consumers make large, real decisions and have the opportunity to learn from experiences? We report on a field experiment designed to address this question. Incumbent clients of a lender in South Africa were sent letters offering them large, short-term loans at randomly chosen interest rates. Psychological features on the letter, which did not affect offer terms or economic content, were also independently randomized. Consistent with standard economics, the interest rate significantly affected loan take-up. Inconsistent with standard economics, the psychological features also significantly affected take-up. The independent randomizations allow us to quantify the relative importance of psychological features and prices. Our core finding is the sheer magnitude of the psychological effects. On average, any one psychological manipulation has the same effect as a one half percentage point change in the monthly interest rate. Interestingly, the psychological features appear to have greater impact in the context of less advantageous offers. Moreover, the psychological features do not appear to draw in marginally worse clients, nor does the magnitude of the psychological effects vary systematically with income or education. In short, even in a market setting with large stakes and experienced customers, subtle psychological features that normatively ought to have no impact appear to be extremely powerful drivers of behavior.
Keywords: D01; C93; D12; D21; D81; D91; M37; O12; 330; Behavioral economics; psychology; microfinance; marketing; field experiment; credit markets; Verhaltensökonomik; Wirtschaftspsychologie; Verbraucherkredit; Test; Südafrika; Mikrofinanzierung